Direct Suits and Derivative Actions: Rethinking Shareholder Protection in Comparative Corporate Law - Alan K Koh (Washington University Global Studies Law Review, 2022)
Shareholder lawsuits comprise two categories: direct suits and derivative actions. While singling out derivative actions as the quintessential minority shareholder protection mechanism, comparative corporate law scholarship, “Law and Finance” literature, and the World Bank’s influential Doing Business reports have all failed to appreciate fundamental legal and functional differences between derivative actions and direct suits, as well as the value of direct suits as shareholder protection mechanisms. Consequently, one of the world’s most powerful and influential institutions perpetuates a misleading view of shareholder protection around the world and promotes reforms that fail to achieve the desired policy objectives. This Article offers a functional, comparative framework of shareholder lawsuits, and a taxonomy of direct suits that classifies how different types provide legal redress against diverse harms to shareholder interests. Drawing on examples from leading civil and common law jurisdictions in the Asia-Pacific, Europe, and North America, this Article shows that direct suits protect shareholders by providing some tangible advantage or alleviation of some specific detriment to the shareholder-plaintiff, shareholders generally, or both, through a wide range of monetary and non-monetary outcomes. Through this comparative analysis of direct suits in diverse jurisdictions, this Article sheds new light on the utility of direct suits for protecting minority shareholders and underscores the perils that arise when persons unskilled in comparative law engage in applied comparative law.